Finland : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Finland. (IMF Staff Country Reports; Country Report, 2022)
With strong policy support, Finland suffered a relatively mild economic contraction in 2020 followed by a swift recovery in 2021. Medium-term growth prospects are less strong, due to adverse demographics and low productivity growth-trends that precede the pandemic. Public debt has increased due to pandemic-related support and will remain on a rising trajectory in the medium term, largely reflecting permanent spending increases.